Survey of Malaysian Critical Intensive Care unit nurses’ awareness of patients’transition experiences (PE) and transitionalcare practice (TCP) - Mohamed Ludin, Salizar; Parker, Steve; Arbon, Paul (Elsevier Ltd., 2014)
careSummaryBackground: Preparation of critically ill patients throughout their transition experiences in Criti-cal Intensive Care Units (CICU) and following discharge can impact upon their recovery. However,there is little research addressing critical care nurses’ awareness of patients’ transition expe-riences.Aim: This study aimed to examine CICU nurses’ awareness of patients’ transition experiencesand transitional care practice in Malaysia.Method: A descriptive questionnaire was used to survey Registered Nurses in seven CICUs in fourhospitals in Malaysia. Data were analysed using descriptive statistics and correlation analysis.Results: The survey had a response rate of 65.2% (178 of 273 eligible nurses). The respondents’mean age was 29.6 years. Most of the respondents were from public hospitals and the majorityhad one to five years’ experience working as Registered Nurses, and in CICU. Public teach-ing hospital nurses had greater awareness of patients’ transition experience (PE) (p < 0.05),and of transitional care practice (TCP) (p < 0.05) than public hospital nurses. Nurses with >10years Critical Intensive Care Unit experience (p < 0.05) had greater awareness of both PE andTCP (p < 0.05). Attending a course of any kind did not affect nurses’ awareness in both PE andTCP (p > 0.05). There was a positive correlation between nurses’ awareness of patients’ transi-tion experience and its impact, and their awareness of transitional care practice performance(rs= 0.42, p < 0.05).Conclusion: CICU nurses need targeted transition education to enable them to anticipate patients’ transitional experiences and to provide appropriate transitional care, particularly for public hospital nurses. Nursing schools need to integrate more content about critically ill patients’ transition experiences into the curriculum, to ensure graduate nurses will be able to anticipate the patient’s experience and provide appropriate transitional care.